Asia, beyond the miracle [videorecording] - Westfall, Matthew; Megalos, Bill; McDowell, Malcolm 1943- (Asian Development Bank, 1997)
This film illustrates the great economic gains that have been achieved, and the tremendous challenges that remain if this is to be sustained. It has benn shot on location in Hong Kong, India, Indonesia, Republic of Korea, nepal and Philippines.